Development of Sasak Folktale-Based Animated Audiovisuals to Improve Storytelling and Literacy Skills in Early Childhood - Azalia Rizkini Pratiwi; Fahruddin Fahruddin; Moh. Irawan Zain (Academia Open, 2026)
Early childhood literacy and storytelling skills are critical foundations for later academic achievement, yet many learning environments remain constrained by monotonous instructional practices and limited culturally responsive media. This study addresses this gap by examining the impact of animated folklore as an innovative learning medium for early childhood education. The aim of the research is to evaluate the effectiveness of folklore-based animated audiovisuals in improving literacy and storytelling skills among young children. The study employs a research and development approach using the ADDIE framework, involving expert validation and field implementation. Empirical data were collected from 65 kindergarten children aged 5–6 years across small-scale and large-scale trials, using observation instruments, questionnaires, and pretest–posttest assessments. Quantitative analysis included descriptive statistics, N-Gain scores, and paired-sample t-tests. The results demonstrate substantial improvements in both literacy and storytelling outcomes after exposure to the animated folklore intervention, with medium-to-high learning gains and statistically significant differences between pretest and posttest scores. The media achieved high validity and practicality ratings from experts, teachers, and learners, indicating strong instructional quality and classroom feasibility. The novelty of this study lies in its integration of culturally grounded animated folklore as a systematic pedagogical tool that simultaneously strengthens narrative competence and early literacy skills. The findings contribute to early childhood education theory by reinforcing the role of culturally responsive digital media in language development, while offering practical implications for educators and policymakers seeking scalable, engaging strategies to enhance foundational literacy and storytelling in early learning contexts. Highlights: Animated folklore significantly improves early childhood literacy and storytelling performance Culturally responsive animation increases learner engagement and narrative competence Digital storytelling media provides effective, scalable support for early childhood education Keywords: Early Childhood Literacy, Storytelling Skills, Animated Folklore, Culturally Responsive Learning, Audiovisual Education